The guide to railway masonry containing a complete treatise on the oblique arch - Nicholson, Peter (Groombridge, 1846)
The third edition of a 19th-century text on railway masonry, sections cover the angle of twist, radius of curvature, use of the trihedral and many other geometrical topics.